The case for solar full-disk spectral diagnostics: Chromosphere to corona - Ugarte-Urra, Ignacio; Young, Peter R.; Brooks, David H.; Warren, Harry P.; De Pontieu, Bart; Bryans, Paul; Reep, Jeffrey W.; Downs, Cooper; Winebarger, Amy R.; Tun, Samuel D. (Frontiers in Astronomy and Space Sciences, 2023)
In the context of the recent call for white papers for the Decadal Survey for Solar and Space Physics (Heliophysics) 2024-2033, we present the argument that spatially-resolved spectral diagnostics over the full solar disk should be made a high-priority goal in Heliophysics and lead to the development of a mission concept that has the potential to become a cornerstone of the Heliophysics System Observatory (HSO). We claim that a mission providing consistent full-disk sampling of plasma properties (Doppler-shifts, non-thermal velocities, electron densities, elemental composition, etc.) of the chromosphere-corona system at the dynamic timescales of solar eruptive phenomena will revolutionize the field by adding the spectral diagnostics capability to the highly successful concept of full-disk imaging, everywhere, all the time, represented by the Solar Dynamics Observatory (SDO). We argue for it to be developed by the end of the current Decadal Survey cycle around the lessons learned from spectroscopic missions in the current NASA development pipeline, that include innovative strategies for faster integration of large fields-of-view, and comprehensive temperature coverage.